Birkbeck University of London, University of Nicosia, University of Nicosia Cyprus - (:unkn) unknown (My University, 2026)
Troubled Contemporary Art Practices in the Middle East: Post-Colonial Conflicts Pedagogies of Art History, and Precarious Artistic Mobilization, organized by Birkbeck University of London, University of Nicosia, University of Nicosia Cyprus 3-4 June 2016. “Socially engaged art across the Mediterranean Sea: 2001/51/EC – Embodied Crossings - Now Boarding.”